Use of pragmatic and explanatory trial designs in acute care research: lessons from COVID-19. Issue 7 (July 2022) - Casey, Jonathan D; Beskow, Laura M; Brown, Jeremy; Brown, Samuel M; Gayat, Étienne; Ng Gong, Michelle; Harhay, Michael O; Jaber, Samir; Jentzer, Jacob C; Laterre, Pierre-François; Marshall, John C; Matthay, Michael A; et al.
Summary: Unique challenges arise when conducting trials to evaluate therapies already in common clinical use, including difficulty enrolling patients owing to widespread open-label use of trial therapies and the need for large sample sizes to detect small but clinically meaningful treatment effects. Despite numerous successes in trials evaluating novel interventions such as vaccines, traditional explanatory trials have struggled to provide definitive answers to time-sensitive questions for acutely ill patients with COVID-19. Pragmatic trials, which can increase efficiency by allowing some or all trial procedures to be embedded into clinical care, are increasingly proposed as a means to evaluate therapies that are in common clinical use. In this Personal View, we use two concurrently conducted COVID-19 trials of hydroxychloroquine (the US ORCHID trial and the UK RECOVERY trial) to contrast the effects of explanatory and pragmatic trial designs on trial conduct, trial results, and the care of patients managed outside of clinical trials. In view of the potential advantages and disadvantages of explanatory and pragmatic trial designs, we make recommendations for their optimal use in the evaluation of therapies in the acute care setting.